ON DIVERGENCE OF FOURIER–WALSH SERIES OF CONTINUOUS FUNCTION - Sargsyan, S.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
We prove that for any perfect set P of positive measure, for which 0 is a density point, one can construct a function f (x) continuous on [0, 1) such that each measurable and bounded function, which coincides with f (x) on the set P has diverging Fourier–Walsh series at 0.